Lorenzo Johnston Greene papers - Greene, Lorenzo J. (Lorenzo Johnston), 1899-1988.
Chiefly academic files documenting Greene's career as a professor of history and pioneer in the field of African American studies at Lincoln University, Jefferson City, Mo. Academic files include correspondence, memoranda, minutes of meetings, grant proposals, student writings, course and curricula material, bibliographies, news releases, reports, subject files, archival resources on African Americans, drafts of books, statistical files, legal documents, and other research material. Family papers include correspondence, address books, biographical material, legal papers, concert programs, and other papers. The Speeches and Writings file includes speeches; writings by Greene and others including articles, books, dissertations, diaries, poems, and song lyrics; and transcripts of interviews and panel discussions. Also includes files for professional and public interest organizations. Records of Midwest Journal, a periodical emphasizing research in African American studies and writings which Greene edited from 1947 to 1956, include correspondence, manuscript articles, short stories, poems, transcripts, biographical material, galleys, and subscription and circulation lists.
Documents Greene's work with Carter G. Woodson and Charles H. Wesley of the Association for the Study of Negro Life and History, Inc.; his publications and research on African Americans in general, particularly in colonial New England; and his role as a consultant to Parting Ways, the Museum of Afro-American Ethnohistory, Plymouth, Mass. Civil rights and community activities documented include sharecroppers' roadside demonstrations in southern Missouri (1939-1940); advocacy for open housing, school desegregation, and multicultural representation in textbooks; and Greene's work with organizations such as the Missouri Advisory Committee to the United States Commission on Civil Rights, Missouri Association for Social Welfare, Missouri Commission on Human Rights, Institute for Drop-Out Prevention and Teacher Orientation, Kansas City, Mo., and Institute to Facilitate Desegregation in the Kansas City, Mo., Public Schools. The concert career of Greene's wife, pianist Thomasina T. Greene, is reflected in the family papers.
Correspondents include Marjorie E. Anderson, Herbert Aptheker, Clarence Albert Bacote, Thomas Hart Benton, Cecil A. Blue, Andrew F. Brimmer, Mary E. Brooks, Adelaide M. Cromwell, Gerald L. Davis, Herman Dreer, W. E. B. Du Bois, William L. Dunn, Mervyn M. Dymally, Merl R. Eppse, John E. Fleming, Charles W. Florence, James Frank, John Hope Franklin, Jacqueline Anne Goggin, H. Hadley Hartshorn, J. Noel Heermance, Harvey H. Jackson, Luther Porter Jackson, W. B. Jason, Charles Spurgeon Johnson, Harold J. Jones, Lois Mailou Jones, Peter Kellogg, Charles L. Klotzer, Ulysses Lee, Rayford Whittingham Logan, Wilbur C. McAfee, Paul McStallworth, Louis R. Mehlinger, August Meier, M. Sammye Miller, Edward Alexander Parsons, Benjamin Quarles, Lawrence Dunbar Reddick, Richard E. Risk, William P. Robinson, Patricia W. Romero, George Shepperson, Bert Shulimson, Mabel M. Smythe, Arvarh E. Strickland, Charles W. Thomas, Harcourt A. Tynes, Raleigh Wilson, and Marion Manola Thompson Wright.
Microfilm edition of U.S. Army Colored Infantry, 18th Regiment records, circa 1863-circa 1865 (reel 1) and Missouri volunteer regiments registers of deaths, 1861-1865 (reel 2), available only on microfilm
Microfilm of originals in the National Archives and Records Administration (Washington, D.C.)
National Archives and Records Administration
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
African American historian, educator, editor, and civil rights and social activist.
Keywords: Anderson, Marjorie E. -- Correspondence; Aptheker, Herbert, -- 1915-2003 -- Correspondence; Bacote, Clarence Albert, -- 1906- -- Correspondence; Benton, Thomas Hart, -- 1889-1975 -- Correspondence; Blue, Cecil A. -- Correspondence; Brimmer, Andrew F. -- Correspondence; Brooks, Mary E. -- Correspondence; Cromwell, Adelaide M. -- Correspondence; Davis, Gerald L. -- Correspondence; Dreer, Herman, -- 1889- -- Correspondence; Du Bois, W. E. B. -- 1868-1963 -- Correspondence; Dunn, William L., -- 1919- -- Correspondence; Dymally, Mervyn M., -- 1926-2012 -- Correspondence; Eppse, Merl R. -- 1893- -- Correspondence; Fleming, John E. -- 1944- -- Correspondence; Florence, Charles W. -- Correspondence; Frank, James, -- 1930- -- Correspondence; Franklin, John Hope, -- 1915-2009 -- Correspondence; Goggin, Jacqueline Anne, -- 1953- -- Correspondence; Greene, Thomasina T. -- 1913-; Hartshorn, H. Hadley -- 1909- -- Correspondence; Heermance, J. Noel -- Correspondence; Jackson, Harvey H. -- Correspondence; Jackson, Luther Porter, -- 1892-1950 -- Correspondence; Jason, W. B. -- Correspondence; Johnson, Charles Spurgeon, -- 1893-1956 -- Correspondence; Jones, Harold J. -- Correspondence; Jones, Lois Mailou -- Correspondence; Kellogg, Peter -- Correspondence; Klotzer, Charles L. -- Correspondence; Lee, Ulysses -- Correspondence; Logan, Rayford Whittingham, -- 1897-1982 -- Correspondence; McAfee, Wilbur C. -- Correspondence; McStallworth, Paul -- Correspondence; Mehlinger, Louis R. -- Correspondence; Meier, August, -- 1923- -- Correspondence; Miller, M. Sammye -- Correspondence; Parsons, Edward Alexander, -- 1878-1962 -- Correspondence; Quarles, Benjamin -- Correspondence; Reddick, Lawrence Dunbar, -- 1910- -- Correspondence; Risk, Richard E. -- Correspondence; Robinson, William P., -- 1911- -- Correspondence; Romero, Patricia W. -- Correspondence; Shepperson, George -- Correspondence; Shulimson, Bert -- Correspondence; Smythe, Mabel M. -- Correspondence; Strickland, Arvarh E. -- Correspondence; Thomas, Charles W., -- 1926- -- Correspondence; Tynes, Harcourt A. -- Correspondence; Wesley, Charles H. -- 1891-1987.; Wilson, Raleigh -- Correspondence; Woodson, Carter Godwin, -- 1875-1950.; Wright, Marion Manola Thompson, -- 1904-1962 -- Correspondence; Association for the Study of Negro Life and History, inc; Institute for Drop-Out Prevention and Teacher Orientation (Kansas City, Mo.); Institute to Facilitate Desegregation in the Kansas City, Mo., Public Schools; Lincoln University (Jefferson City, Mo.); Missouri Association for Social Welfare; Missouri Commission on Human Rights; Parting Ways, the Museum of Afro-American Ethnohistory (Plymouth, Mass.)